Human-AI Collaboration in Pharmacy Decision Systems: Transforming Healthcare through Intelligent Partnership - Ram Mohan Reddy Pothula, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Human-AI collaboration in pharmacy decision systems represents a transformative approach to pharmaceutical care, leveraging the complementary strengths of artificial intelligence and pharmacist expertise. This partnership enhances medication management through intelligent decision support systems that analyze vast datasets while preserving critical human judgment. The integration of predictive analytics enables proactive intervention for patients at risk for adverse events or non-adherence, while natural language processing extracts valuable insights from unstructured clinical documentation. Despite implementation challenges, including technical integration issues and ethical considerations surrounding bias and privacy, the synergistic relationship between AI capabilities and pharmacist clinical reasoning is reshaping pharmacy practice. As these technologies evolve, they promise to augment rather than replace pharmacists, allowing these healthcare professionals to focus on complex clinical decisions and patient engagement while AI handles computational tasks. This collaborative model maintains the essential human elements of healthcare delivery while harnessing technological advances to improve medication safety, operational efficiency, and patient outcomes.
Keywords: Pharmacy artificial intelligence; Clinical decision support systems; Predictive medication analytics; Natural language processing in pharmacy; Human-AI healthcare collaboration